Technology acceptance of financial technology (fintech) for payment services among employed fresh graduates / Shamsurin Ahmad, Sharina Tajul Urus and Sharifah Nazatul Faiza Syed Mustapha Nazri - Ahmad, Shamsurin; Tajul Urus, Sharina; Syed Mustapha Nazri, Sharifah Nazatul Faiza (Universiti Teknologi MARA, 2021)
The Fourth Industrial Revolution (IR 4.0), which is complementary to the technological revolution, has given birth to Financial Technology (Fintech). Numerous advantages are offered by Fintech, yet the adoption rate is still low. This is especially from the employed fresh graduates' perspectives that are regarded as the computer literate and IT savvy's group. This research aims to examine the factors that affect the technology acceptance of Fintech payment services. The research attempts to measure the relationships between performance expectancy, effort expectancy, social influence, facilitating condition and consumers' trust with the adoption of Fintech. Based upon the Unified Theory of Acceptance and Use of Technology (UTAUT), the quantitative method was employed via online survey of 179 respondents. The result showed that consumers' trust had the highest impact on the adoption of Fintech payment services, followed by performance expectancy and effort expectancy. In contrast, facilitating conditions and social influence showed an insignificant relationship with the adoption of Fintech payment services. This finding would enhance the awareness for people to become more open towards the acceptance of Fintech for their daily transactions. Fintech companies are expected to develop into more secure services and design better products in becoming a cashless society.